1977
DOI: 10.1148/122.2.405
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of99mTechnetium Polyphosphate in Fibrothorax following Pneumonectomy

Abstract: Following the injection of 99mTechnetium-polyphosphate for bone scanning, a diffuse accumulation of radioactivity in post-pneumonectomy fibrothorax was demonstrated in 3 patients. This substantiates the nonspecificity of the localization of 99mTc-phosphorus compounds, and underlines the need for close clinical correlation in the accurate interpretation of such scans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1979
1979
1990
1990

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Collagen-formation and activated phosphatase in effusion might also be related to the localization of 99 mTc-MDP. 13 In our study, 99mTc-MDP accumulation in pleural effusion was noted not only in patients with malignant effusion, but also with benign effusion, with almost the same positive rate. Especially there was a diffuse uptake of the radiotracer in all of 3 patients with effusion due to congestive heart failure, and also 2 patients with thoracotomy.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Collagen-formation and activated phosphatase in effusion might also be related to the localization of 99 mTc-MDP. 13 In our study, 99mTc-MDP accumulation in pleural effusion was noted not only in patients with malignant effusion, but also with benign effusion, with almost the same positive rate. Especially there was a diffuse uptake of the radiotracer in all of 3 patients with effusion due to congestive heart failure, and also 2 patients with thoracotomy.…”
Section: Discussionsupporting
confidence: 70%
“…Non-osseous uptake by skeletal agents is a well-known fact and some investigators have reported diffuse intrathoracic accumulation of skeletal agents in several disease states such as metastatic calcification, 8-10 pleural effusion, 4-7 radiation pneumonitis,lt alveolar microlithiasis 12 and fibrothorax. 13 Levy and Park14 reported that unilateral thoracic soft-tissue accumulation of bone agents was present in 60 of 130 (46 %) of patients with lung cancer. In that study, they emphasized that radiation therapy for lung tumors was the most significant of the factors studied in unilateral soft-tissue uptake of bone agents in the thorax of patients with lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Their theory is supported by the localisation of bone-seeking agents in healing surgical scars (Poulose et al 1975) and in fibrothorax (Ravin et al 1977).…”
Section: Imagingmentioning
confidence: 95%